From vision to impact: Strategic school leadership. (2nd May 2021) - Solly, Ben
Abstract : A school's strategic education plan brings together its vision and values, achieving buy-in from the staff and community. In this Best Practice Focus, headteacher Ben Solly sets out his approach and offers practical advice. He discusses his vision, values and priorities, how to create highly effective teams, and how this all links to impact and outcomes